If p(x) = x + 3, then find p(x) + p (-x)? (a) 10 (b) 12 (c) 6 (d) 18​

Question

If p(x) = x + 3, then find p(x) + p (-x)?
(a) 10
(b) 12
(c) 6
(d) 18​

in progress 0
Allison 1 month 2021-08-18T20:15:03+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-18T20:16:04+00:00

    Answer:

    P(x) = x + 3

    then P ( x ) = x + 3

    Now let’s substitute

    p (x) + p (x ) = x + 3 x + 3

    => 6

    Hence option (c) is the answer !!!!

    Hope this helps you

    0
    2021-08-18T20:16:41+00:00

    p(x)+ p(-x) =x+3+-x+3

    =6

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )